If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = x + 4 + -9x Reorder the terms: 0 = 4 + x + -9x Combine like terms: x + -9x = -8x 0 = 4 + -8x Solving 0 = 4 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 0 + 8x = 4 + -8x + 8x Remove the zero: 8x = 4 + -8x + 8x Combine like terms: -8x + 8x = 0 8x = 4 + 0 8x = 4 Divide each side by '8'. x = 0.5 Simplifying x = 0.5
| 2.6=-5.2(3.4+x) | | 0.1x=1.4 | | 34=-0.4(x+22) | | -0.26=logx | | -4(-5-b)= | | 3(x-9)=6(x+3) | | sinx=-0.95 | | 10x+15x-8+3=-2x+3-8 | | 7p-8=-3p+6 | | 2=4y-2y-6 | | 6e-15=15 | | x+37=3x+9 | | (x-8)+23-4=36 | | 42=28-3c | | 5k+26=1 | | -3e^1-x=11 | | (-r^2)+4(-r)-4=-8 | | 6-c=3 | | 7/8x-1/3y=3 | | 7x-6.4-0.1x+3.7x-1= | | q^2-8q+20=0 | | q^2-81+20=0 | | X-4x=-6-3 | | X^2-x+5=41 | | X^2-x+5=3 | | sn=n^2 | | -30.07/-0.02 | | x^2+2xy+y^2-y= | | x^2+2xy+y^2-y=0 | | 6x^2+9=12 | | 0.26-0.02(x+2)=-0.04(2-x) | | 2z/10-9=-8 |